2023
DOI: 10.1001/jamanetworkopen.2023.13879
|View full text |Cite
|
Sign up to set email alerts
|

Associations Between Vascular Risk Factor Levels and Cognitive Decline Among Stroke Survivors

Abstract: ImportanceIncident stroke is associated with accelerated cognitive decline. Whether poststroke vascular risk factor levels are associated with faster cognitive decline is uncertain.ObjectiveTo evaluate associations of poststroke systolic blood pressure (SBP), glucose, and low-density lipoprotein (LDL) cholesterol levels with cognitive decline.Design, Setting, and ParticipantsIndividual participant data meta-analysis of 4 US cohort studies (conducted 1971-2019). Linear mixed-effects models estimated changes in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 64 publications
0
6
0
Order By: Relevance
“…Evidence can be found that post-stroke patients with elevated FBG may suffer from accelerated cognitive decline due to cerebral microvascular injury, inflammation, oxidative stress, and neurodegeneration [32].…”
Section: Discussionmentioning
confidence: 99%
“…Evidence can be found that post-stroke patients with elevated FBG may suffer from accelerated cognitive decline due to cerebral microvascular injury, inflammation, oxidative stress, and neurodegeneration [32].…”
Section: Discussionmentioning
confidence: 99%
“… 10 These cohorts had ≥50 participants with physician-adjudicated acute stroke during follow-up and SBP and cognition measures pre- and post-stroke. 11 …”
Section: Methodsmentioning
confidence: 99%
“…We included participants with self-reported history of stroke at cohort baseline in the primary analysis as their inclusion did not change estimates of an acute stroke’s effect on cognitive trajectories controlling for pre-stroke cognition. 1 , 11 We performed a sensitivity analysis excluding participants with a selfreported history of stroke at cohort baseline.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the Original Investigation “Associations Between Vascular Risk Factor Levels and Cognitive Decline Among Stroke Survivors,” published May 17, 2023, there were errors in the Methods and Results sections, the Figure, and Table 1. These sections should have stated that all observed glucose levels, rather than fasting glucose levels, were used.…”
mentioning
confidence: 99%